(3GdeMGSHI GdVQjHjI (B/s - (3GdQaGYj, Ndjds ((3YeGf(B: s (3OGQ GdHOGjI(B, s, 2009)
(3eONd Gdi GdeMGSHI GdVQjHjI h CgOGa GdfXGe GdVQjHj GdCQOfj , JMdjd GdhYGA GdVQjHj , GdONhd GdNGVYI ddVQjHI h GdONhd GdeYaGg ef VQjHI GdONd , JfRjd fabGJ GdYed , GdJfRjdGJ h GdGYaGAGJ GdTNUjI h GdbGfhfjI , CSYGQ GdVQjHI , eQGMd JbOjQ VQjHI GdONd h Gdecdahf HJbOje cTa GdJbOjQ GdPGJj , GdJbOjQ aj MGdI GdJNda Yf JbOje cTa GdJbOjQ , JMUjd VQjHI GdONd h GdQjGOGJ , GdLQGFe h GdYbhHGJ (B: (3ZQGeI JCNjQ JbOje cTa GdJbOjQ , GdYbhHGJ h GdeNGdaGJ , MUjdI VQjHI GdONd , JWHjbGJ YedjI h CSFdI ZjQ eMdhdIs
(3eQGLY U(B.264s
Keywords: (3GdVQGFHs; (3GdeMGSHIs; (3GdeMGSHI GdVQjHjIs